Analisis Pengaruh Rasio Permodalan, Rentabilitas dan Profitabilitas Terhadap Harga Saham Bank Digital Indonesia Tahun 2018-2022 - Ayu Dinda Lestari; Purwanti (Prosiding SEMANIS: Seminar Manajemen Bisnis, 2024)
Financial ratios are comparative figures in financial statements that aim to determine the financial position of a company. With this ratio we can also compare the performance of one company with other companies between periods. Good company performance will certainly affect the size of the share price. The share price is a price set by a company for anyone who wants to have the right to become a share owner. The value of this share price is influenced by demand and supply between sellers and buyers of shares. The price of a stock will change at any time, this is due to the good and bad performance of a company. Therefore, the purpose of this study is to analyze the effect of the company's financial ratios on the company's stock price. The financial ratios analyzed in this study are Capital Ratio (CAR), Rentability Ratio (LAR) and Profitability Ratio (ROE). This research was conducted on 5 digital banks in Indonesia in 2018-2022. This sampling is done using purposive sampling method. The statistical testing tool used is SPSS (Statistical Package for the Social Sciences). The results of this study in accordance with the initial hypothesis show that the Current Adequacy Ratio (CAR) has a positive and significant effect on stock prices. Meanwhile, Loan to Asset Ratio (LAR) and Ratio On Equity (ROE) have no significant effect on stock prices in contrast to the initial hypothesis.